Civil Society And Electoral Politics; Nahdlatul Wathan Diniyah Islamiyah (NWDI) in the Victory of Zulkieflimansyah-Siti Rohmi Djalillah in the 2018 NTB ElectionMuh. Samsul Anwar*, Muhammad Fariqh Khatami* - Muh. Samsul Anwar; Muhammad Fariqh Khatami (Yayasan Adra Karima Hubbi, 2024)
This paper discusses the role of Nahdlatul Wathan Diniyah Islamiyah (NWDI) in the victory of the Zulkiflimansyah-Siti Rohmi Djalillah (Zul-Rohmi) pair in the 2018 NTB regional election. Zulkiflimansyah-Siti Rohmi Djalillah (Zul-Rohmi) in the 2018 NTB regional election. The research This research aims to find out the role of NW in Zul-Rohmi's victory and the reasons why NW placed its cadre as Cawag. NW placed its cadre as Cawagub. This research uses a qualitative method qualitative method with data collection techniques of documentation and interviews. Theories used in this research are used in this research are theories of civil society, political parties, and elections, and elections. Results The results of this study show the significant role of NWDI as a civil society in political contestation (Pilkada) 2018. in the 2018 political contestation (Pilkada). In the election, the pair zul-Rohmi, supported by NWDI, won the contestation. The influence of The influence of the leader of the NWDI organization has a big role in attracting votes. The existence of Tuan Guru Bajang (TGB) who is the leader of NWDI has a strong influence in mobilizing his congregation to vote for Zulkul-Rohmi. in mobilizing his congregation to vote for Zulkieflimansyah-Siti Rohmi Djalillah. The influence of TGB was also seen in the contestation of the previous period which also won the NTB Provincial Election. As for the reason NWDI placed its cadre as a candidate for deputy governor, not as a candidate for governor, is due to the socio-cultural conditions of the NTB community. the socio-cultural conditions of the people of NTB who still adhere to a patriarchal culture that does not want women leaders and the experience factor. patriarchal culture that does not favor women leaders and the experience factor of its cadres.